Implementation of the Account National - CUN in the ICBF (2015)
Implementation of the Account National in the ICBF brought uncertainty, given that this institution has the privilege to raise their own resources and to own administrative and financial autonomy, but with the implementation of this system that is responsible for centralize resources generated by the State in a Central Treasury, these will be administered by the National Treasury, it is certainly noteworthy that this system benefits the management of national resources through optimization, avoiding unnecessary borrowing by the state and eliminating the seasonality in bank accounts.